LILIN AROMA TERAPI: PEMANFAATAN LIMBAH MINYAK JELANTAH SEBAGAI UPAYA KEPEDULIAN TERHADAP LINGKUNGAN - Fikri, Ali; Jamaludin, Jamaludin; Junaedi , Nurasikin; Alifia, Yolla; Kusuma, Jaka Wijaya; Simbolon, Silviana (LPPM Universitas Bina Bangsa, 2024)
Every household produces used cooking oil. Generally, used cooking oil is disposed of into the environment without any environmentally sound control. This situation is exacerbated by the lack of public knowledge regarding the impact of used cooking oil on health and the environment. Many people still don't know about the use of used cooking oil, even though it has extraordinary economic value. Therefore, it is important to understand the use of used cooking oil in the household environment. There is a need for innovation in the use of used cooking oil waste into products with economic value. The innovation is provided in the form of knowledge exchange with the public regarding the use of used cooking oil waste into aromatherapy candle products. This activity was carried out during the 2024 High Mandiri Mutual Cooperation Village Development Program (PTMGRMD). This activity aims to provide education to mothers about the use of used cooking oil in other forms, one of which is making aromatherapy candles at the Kampung Baru hall, Cikedal, Pandeglang Banten. The activity participants consisted of 21 mothers, taking place through methods, discussions, demonstrations and direct practice. The results of this service activity show that the participants were very enthusiastic and listened throughout the process and that the participants were active when carrying out the practice. After this activity takes place, it is hoped that mothers will become more aware of the dangers of using used cooking oil and can use used cooking oil into a more useful product.